Encountering Mary From La Salette to Medjugorje. - Zimdars-Swartz, Sandra L. (Princeton : Princeton University Press, 2014)
In the past two centuries hundreds of apparitions of the Virgin Mary have been reported, drawing crowds to the seers and the sites and constituting events of great religious significance for millions of people worldwide. Here Sandra Zimdars-Swartz provides a detective-like investigation of the experiences and interpretations of six major apparitions, including those at La Salette and Lourdes in France during the mid-nineteenth century; at Fatima, Portugal, in 1917; and the more recent ones at San Damiano, Italy; Garabandal, Spain; and Medjugorje, Yugoslavia, where the apparitions continue.
Cover; Part I: Apparitions as Religious Experience; Part II: Apparitions as Religious Knowledge
Description based upon print version of record.
Keywords: Mary, -- Blessed Virgin, Saint -- Apparitions and miracles -- History -- 19th century; Mary, -- Blessed Virgin, Saint -- Apparitions and miracles -- History -- 20th century; RELIGION / Christian Theology / Christology; Electronic books